2000
DOI: 10.2135/cropsci2000.4061724x
|View full text |Cite
|
Sign up to set email alerts
|

Grazing Termination Date Influence on Annual Ryegrass Seed Production and Reseeding in the Southeastern USA

Abstract: Production costs could be reduced if annual ryegrass (Lolium multiflorum Lam.) could be managed for reseeding. Spring grazing termination dates (GTD) of 31 March, 14 April, 28 April, and 12 May were evaluated on seven cultivars for two growing seasons to study spring seed production and volunteer reseeding the following autumn in northeast Texas. There were year × GTD × cultivar interactions for spike density, seed yield, seed weight per spike, and volunteer seedling density and a year × GTD interaction for 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 4 publications
3
15
0
Order By: Relevance
“…Annual ryegrass is one of the most widely used cool season annual in pastures in the southeastern USA (Evers and Nelson, 2000) and its compatibility with clovers in mixtures, particularly white clover, is reported to be poor due to its aggressiveness under favorable conditions (Annicchiarico and Berardo, 1993). However, growing this grass as an adjacent monoculture in the same paddock has been suggested as a viable alternative, which has prompted several studies of their interactions between system components (Kennedy et al, 2007).…”
Section: Chapter V Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Annual ryegrass is one of the most widely used cool season annual in pastures in the southeastern USA (Evers and Nelson, 2000) and its compatibility with clovers in mixtures, particularly white clover, is reported to be poor due to its aggressiveness under favorable conditions (Annicchiarico and Berardo, 1993). However, growing this grass as an adjacent monoculture in the same paddock has been suggested as a viable alternative, which has prompted several studies of their interactions between system components (Kennedy et al, 2007).…”
Section: Chapter V Discussionmentioning
confidence: 99%
“…There are several important agronomic characteristics that account for the widespread use and popularity of this forage including high herbage yield, a long growing season, tolerance to a wide range of environmental conditions and grazing practices, rapid seedling establishment, weed suppression, excellent persistence under close grazing, compatibility with several forage legumes and excellent forage quality and palatability (Jung et al, 1996;Franca et al, 1998). Optimum growth of annual ryegrass is attained on soils of pH ≥ 5.7 with lower forage production on more acid soils (Evers and Nelson, 2000).…”
Section: Origin and Agronomic Characteristicsmentioning
confidence: 99%
“…The first requirement for successful reseeding is to produce sufficient amount of seed in the spring. Stocking rates may have to be reduced or terminated by a certain date for satisfactory seed production (10). High temperature dormancy in annual ryegrass is the mechanism that prevents summer seed germination (15).…”
Section: Volunteer Reseeding Of Cool‐season Annualsmentioning
confidence: 99%
“…, 2005) and it has a capacity for regeneration through self‐seeding (Prine et al. , 1982; Evers and Nelson, 2000). The ability of IRG to regenerate through seed can make it a persistent weed of winter wheat (Trusler et al.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has demonstrated that with early termination of grazing IRG can be grazed in spring without detriment to subsequent yield of seed (Young et al. , 1996) or to the production of seed sufficient for volunteer reseeding (Evers and Nelson, 2000). However, no estimate has been made of the reduction in herbage production of IRG arising from the early termination of grazing that is necessary to ensure an adequate supply of seed for self‐seeding.…”
Section: Introductionmentioning
confidence: 99%